The Influence of Financial Risk on the Financial Performance of Commercial Banks Listed on the IDX - Syahpria, M Fadly; Putra, Daffa Ikhsan; Lestari, Henny Setyo (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to analyze financial risks, including capital risk, liquidity risk, and operational risk, in relation to financial performance, measured by Return on Assets (ROA) and return on equity (ROE). The study also includes bank size as a control variable in assessing financial performance. The research employs purposive sampling to select samples, focusing on conventional commercial banks listed on the Indonesia Stock Exchange (IDX) over a five-year period from 2019 to 2023. Data were collected from 33 banks and analyzed using descriptive statistiks and a fixed effects model for hypothesis testing. Data analysis was conducted through panel data regression analysis using E-views 9.0. The findings of this study indicate that capital risk does not impact financial performance, liquidity risk has no effect on financial performance, operational risk has a significant negative effect on financial performance, and bank size does not influence financial performance. Based on this research, it is recommended that banks thoroughly evaluate operational risks. Future researchers are encouraged to include additional independent variables and extend the sample period for more accurate results.